2012
DOI: 10.4103/0019-509x.107750
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exposure to second-hand smoke at home and outside the home among students aged 11-17 years: Results from the Mumbai Student Tobacco Survey 2010

Abstract: Self-reported tobacco use status, age, parents' tobacco use, close friends' smoking, and the route they take to school were significant determinants of exposure to SHS at home and outside the home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 11 publications
4
19
0
Order By: Relevance
“…Ten of the 41 studies were conducted in the UK (England [5] , [24] [26] , Scotland [27] [30] , Wales [31] , England and Wales [32] ), eight in the USA [33] [40] , three in Germany [41] – [43] , three in Greece [44] [46] , two in Korea [47] , [48] and one each in Denmark [49] , Sweden [50] , Finland [51] , Norway [52] , Italy [53] , Spain [54] , Puerto Rica [55] , Australia [56] , Malaysia [57] , Mongolia [58] , South Africa [59] , India [60] , Taiwan [61] , Thailand [62] and Tehran [63] .…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the 41 studies were conducted in the UK (England [5] , [24] [26] , Scotland [27] [30] , Wales [31] , England and Wales [32] ), eight in the USA [33] [40] , three in Germany [41] – [43] , three in Greece [44] [46] , two in Korea [47] , [48] and one each in Denmark [49] , Sweden [50] , Finland [51] , Norway [52] , Italy [53] , Spain [54] , Puerto Rica [55] , Australia [56] , Malaysia [57] , Mongolia [58] , South Africa [59] , India [60] , Taiwan [61] , Thailand [62] and Tehran [63] .…”
Section: Resultsmentioning
confidence: 99%
“…[1] In a study done among school children in Mumbai, 16.5% of students were exposed to secondhand smoke at home and 39.9% of students were exposed to secondhand smoke outside their homes. [13] The figure was 42% for adults in Kerala state.…”
Section: Discussionmentioning
confidence: 99%
“…One such study was conducted in Mumbai in 2010, found that students own tobacco use, their age, their parents tobacco use, their close friends tobacco use were associated with their exposure to second hand smoke at home and outside home. 16 The family members and friends tobacco use was associated with adults 17 and children's 10,14,15,18,19 tobacco use. A population base survey of high school students in Mumbai 19 further delineated that both parents using tobacco increased the odds four times while any one parent using tobacco increased the odds two times that their children will also use tobacco.…”
Section: Discussionmentioning
confidence: 97%
“…Smoking and chewing tobacco has severe influence on social, 11,13-24 economic 13,14,18,21-24 and health [11][12][13][14][15][16][17][19][20][21][22][23][24] components of individuals. Use of tobacco exposes, both the first hand users and second hand smokers, to many harmful carcinogenic chemicals and diseases.…”
Section: Discussionmentioning
confidence: 99%